PEN / BALLPOINT / TYPEWRITER / COMPUTER. REFLECTIONS ON INTELLECTUAL AND POWER IN PERU - Rosario Pacahuala, Emilio (2014)
The relationship between intellectuals and power has been continuously. We see intellectuals who mortgaged his pen in favor of a government and were scathingly against another for the privileges which meant it. Our goal is to make a brief evolution of intellectual emphasizing the Peruvian case. We will use the main authors who have researched on this subject.